2007
DOI: 10.1021/cc700122a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Solid-Phase Synthesis of 3-Substituted-5-Oxo-5H-Thiazolo[2,3-b]-Quinazoline-8-Carboxamides under Mild Conditions with Two Diversity Positions

Abstract: In continuation of our efforts to develop novel and efficient polymer-supported routes, leading to heterocyclic derivatives with potentially attractive pharmacological properties, we turned our attention to thiazolo [2,3,b]quinazolines. A survey of the literature revealed that a quinazoline ring fused with thiazole exhibits a wide range of biological activities, 1-3 including antifungal 4 and antibacterial activities. [4][5][6]3,b]quinazoline derivatives were also tested for their application as herbicides for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…A number of synthetic methods for the preparation of this ring system have been developed. These include reactions between heteroaromatic 2-amino esters and 2-(methylthio)-2-thiazoline, [15] solid-phase methods, [16] condensations of substituted anthranilic acids or esters with methyl 2-chlorothiazole-5-carboxylate, [17] and the electrochemical oxidation of catechols in the presence of 2-mercapto-3H-quinazolin-4-one. [18] Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
“…A number of synthetic methods for the preparation of this ring system have been developed. These include reactions between heteroaromatic 2-amino esters and 2-(methylthio)-2-thiazoline, [15] solid-phase methods, [16] condensations of substituted anthranilic acids or esters with methyl 2-chlorothiazole-5-carboxylate, [17] and the electrochemical oxidation of catechols in the presence of 2-mercapto-3H-quinazolin-4-one. [18] Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable research efforts have been devoted to synthesizing thiazole, quinazoline derivatives, and their moieties because of their widespread applications of biological merit [ 1 , 2 , 3 , 4 ]. Thiazole and quinazoline exist in condensed fused systems such as thiazolo[3,2- a ]quinazoline, thiazolo[4,3- b ]quinazoline, thiazolo[2,3- b ]quinazoline, 8 H -thiazolo[5,4- f ]quinazolin-9-ones, thiazolo[4,5- h ]quinazolin, and thiazolo[5,4- c ]quinoline which leads to them exhibiting their properties as important synthetic targets [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] due to their biological and pharmacological efficiency, such as DYRKIA inhibitors [ 15 ], HIV-1integrase inhibition [ 16 ], antimalarial [ 17 ], anticancer [ 18 , 19 , 20 ], anti-inflammatory [ 20 , 21 ], antituberculosis [ 22 ], antidepressant [ 23 ], anticonvulsant [ 24 ], antifungal [ 25 ], antihistamine [ 26 ], and antitumor [ 10 , 27 , 28 , 29 ] activity. In addition, these compounds play an important role by providing a new molecular framework for drug discovery [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…So, on the basis of the above findings the quinazoline and thiazole are privileged structures, which attracted considerable attention in the designing of biologically active molecules and combining them in one molecule exemplified by the thiazoloquinazoline system it is expected to furnish biologically active molecule with characteristic features. In the last decade numerous methods have been developed for the synthesis of highly substituted thiazoloquinazoline system exemplified by thiazolo[2,3- b ]quinazoline [8,31-33], thiazolo[5,4- f ]quinazoline [34,35], thiazolo[4,5- h ]quinazolin [36], thiazolo[5,4- c ]quinoline [37], thiazolo[4,3- b ]quinazoline [38] and thiazolo[3,2- a ]quinazoline [39]. However, after detailed literature survey it was observed that there were only limited publications devoted to the synthesis of especially thiazolo[3,2- a ]quinazoline which involved reaction of 2-mercaptopropargyl quinazolin-4-one with various aryl iodides catalyzed by Pd-Cu [39] or by condensation of 2-mercapto-4-oxoquinazoline with chloroacetic acid [40], inspite of this procedure was also reported in the literature to afford the thiazolo[2,3- b ]quinazoline.…”
Section: Introductionmentioning
confidence: 99%